Effect of polyaniline-modified lignosulfonate added to the negative active material on the performance of lead-acid battery. (1st April 2020) - Chen, Chengwei; Liu, Yongchuan; Chen, Yuanqiang; Li, Xin; Cheng, Jian; Chen, Sujing; Lin, Junhong; Zhang, Xiangxin; Zhang, Yining
Abstract: Expanders are important additives for lead-acid battery, which reduce the degree of compaction within negative plates and provide more ionically transport channels within the plates during the charge/discharge process. Lignosulfonates (LS) with a 3D structure is one of the most often used expander, which ensures the low compaction of negative plate. However, the insulativity of LS increase cathodic polarization and retard the conversion of PbSO4 to Pb during charging progress, which intensify the PbSO4 accumulation in the negative plate and shorten the HRPSoC cycle life of the battery. Focusing on the problems, we used polyaniline-modified lignosulfonates (PANI/LS) composites as expanders. The composites inherit good electronic conductivity of PANI and ionic transport channels from the LS with a 3D structure. Furthermore, the PANI/LS composites havea higher hydrogen evolution over-potential than LS, which avoids the electrolyte dry-out during charging process. The battery tests indicate PANI/LS can refine the size of PbSO4 particles and promote the conversion of PbSO4 to Pb. The HRPSoC cycle life of battery with 2PANILS composite expander is 7.3 times longer than that of the battery with LS expander. The negative active material utilization (UNAM ) of the battery containing 2PANILS composite expander is 2 times larger than the battery with LS expander. In addition, the preparation process for the negative plate with 2PANI-LS expander is facile and has potentials for large-scale industrial production. Highlights: Polyaniline-modified lignosulfonates (PANI/LS) composites were first used as expanders in the negative plates for lead-acid batteries. The expanders inherited the conductivity from PANI and the 3D structure from LS. The 2PANI-LS improved the battery's cycle life by 7 times and doubled the negative active materials utilization when compared with the LS.